Шедевры искусства 20 века: альбом / перевод с английского Е. С. Гордон - Гордон Е. С. (АСТ-ЛТД, 1997)
Экземпляры: ЧЗ (20160216) / Инвентарный номер: 37425 / Цена: 195.92 / Сис.шифр: 85.1я6 / Авт.знак: Ш 38 / ГРНТИ: 18 / ББК: 85.1я6